2018
DOI: 10.1161/atvbaha.117.309795
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by Atherogenic Macrophages Transfer MicroRNA to Inhibit Cell Migration

Abstract: EV-derived miRNAs from atherogenic macrophages, in particular miR-146a, may accelerate the development of atherosclerosis by decreasing cell migration and promoting macrophage entrapment in the vessel wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(156 citation statements)
references
References 67 publications
5
151
0
Order By: Relevance
“…Extracellular vesicles (EVs) are now recognized as having an important role in intercellular communication and, contrary to previous beliefs, are not insignificant cellular debris that accumulates with membrane shedding (16)(17)(18). Currently, EVs are classified into 3 main groups, based largely on a specific set of criteria: size, density, protein/lipid composition, and the process underlying release (17,19,20).…”
mentioning
confidence: 99%
“…Extracellular vesicles (EVs) are now recognized as having an important role in intercellular communication and, contrary to previous beliefs, are not insignificant cellular debris that accumulates with membrane shedding (16)(17)(18). Currently, EVs are classified into 3 main groups, based largely on a specific set of criteria: size, density, protein/lipid composition, and the process underlying release (17,19,20).…”
mentioning
confidence: 99%
“…In another study, exosomes secreted by atherogenic macrophages were shown to be able to transfer specific microRNAs, including miR‐146a, to naïve macrophages. Treatment with these exosomes could inhibit the migratory activity of the naïve macrophages, potentially promoting macrophage entrapment in the vessel wall and atherosclerosis …”
Section: Role Of Exosomesmentioning
confidence: 99%
“…Human monocytes can secrete microvesicles containing miRNAs that are uptaken by endothelial cells and increase their migratory capabilities [127]. MiR-150 is contained in monocyte-derived microvesicles, both from the monocytic cell line, THP1, and from human peripheral blood monocytes [60].…”
Section: Control Of Leukocyte Trafficking and Inflammationmentioning
confidence: 99%